Development of a Novel Pathways Program for Pre-Health Students by a Private Four-Year University and a Private Health Professions University. Issue 3 (September 2018) - Funk, Phillip E.; Knott, Patrick; Burdick, Lindsey; Roberts, Michael
Abstract : Abstract: Education in the health professions occurs at the graduate level, increasing the barriers to underrepresented and first-generation students. Some programs attempt to alleviate these barriers by streamlining passage from the undergraduate campus to the medical campus within a university or by accelerating entry to the professions by bypassing the bachelor's degree. These solutions each have their own limitations for students, including added pressure to maintain grades and a limited ability to explore multiple professions. The Alliance for Health Sciences, a partnership between DePaul University and Rosalind Franklin University of Medicine and Science (RFUMS), was formed to address these issues and has created the Pathways Honors program. Through this program, current DePaul students may apply for an early admission decision to one of 6 of RFUMS's programs and, if qualified, pursue an accelerated entry. They have the option to apply for early decision at any time during their undergraduate career to encourage exploration of career options and to allow students to adjust to college rigor with lower stakes. In addition, collaborative, innovative advising contributes to creating well-rounded students and admissions committee decisions not dictated solely by test metrics. The Pathways Honors program has continued to attract a diverse student pool to DePaul, and early indications are that many of these students are making a successful transition to professional programs. Currently, we have data on our first cohort of students. Continued development of this program will be necessary to ensure that it is preparing students for rigorous graduate programs and helping to diversify the health care workforce.